Research Status of Clove, Application of Technology and Development Strategy with Ecological Basic - Setiawan Setiawan; Rosihan Rosman (Perspektif, 2015)
ABSTRACTClove (Syzygium aromaticum L.Marr and Perr) is a native spice crop of Indonesia. Development of clove estate areas has experienced up and downs fluctuation doe to desease and price fluctuation that cause farmers do not maintenat plant. Hence, it is necessary to perform extensification and intensification. Extensification means development through the expansion, while the intensification means development through the improvement of technology. Results of previous studies include land suitability maps and climate, fertilization technology, cropping pattern, maintenance, nurseries and the search for improved varieties have been done. But has not answered the problems of cloves, especially fluctuations in the yield. Extensification efforts require land suitabilityand climate maps, while intensification requires land/environment based technology. Ecology-based cultivation technologies including varieties, planting, fertilizer, maintenance, cropping pattern, harvest and post harvest should be given attention in order to archive effectively, efficiently and high productivity. The criteria of land and climate suitability, and cultivation technology can be used as guidelines for the development of cloves and as a basis for making a map at operational scale and for determining the appropriate technological package. This paper aims to examine the technological research that has been done and integrate into a form more efficient cultivation technology-based ecology (soil and climate) for use as the direction and strategy of the development of clove in the future.Keywords : Clove, technology, ecology, land suitability 28 Volume 14 Nomor 1, Juni 2015 : 27 -36 Status Penelitian, Penerapan Teknologi dan Strategi Pengembangan Tanaman Cengkeh Berbasis Ekologi ABSTRAKCengkeh (Syzygium aromaticum L. Marr. and Perr.) merupakan tanaman rempah asli Indonesia. Perkembangan perkebunan cengkeh mengalami pasang surut akibat adanya serangan penyakit dan fluktuasi harga cengkeh yang menyebabkan petani tidak mau memelihara tanaman. Oleh karena itu diperlukan upaya ekstensifikasi dan intensifikasi. Ekstensifikasi berarti pengembangan melalui perluasan areal sedangkan intensifikasi berarti pengembangan melalui peningkatan teknologi tanaman cengkeh. Hasil penelitian terdahulu antara lain peta kesesuaian lahan dan iklim, teknologi pemupukan, pola tanam, pemeliharaan, pembibitan dan pencarian varietas unggul telah dilakukan. Namun belum menjawab permasalahan cengkeh terutama fluktuasi hasil. Upaya ekstensifikasi diperlukan peta kesesuaian lahan dan iklim sedangkan intensifikasi diperlukan teknologi berbasis kondisi lahan/lingkungan. Teknologi budidaya berbasis ekologi mulai dari varietas, penanaman, pemupukan, pemeliharaan, pola tanam hingga panen dan pasca panen harus mendapat perhatian, karena selain mampu menghasilkan produktivitas yang tinggi, juga efektif dan efisien. Kriteria kesesuaian lahan, iklim dan teknologi budidaya dapat dijadikan pedoman pengembangan tanaman cengkeh dan sebagai dasar pembuatan peta skala operasional dan menentukan paket teknologi yang tepat. Makalah ini bertujuan untuk menelaah teknologi hasil penelitian yang telah dilakukan dan mengintegrasikan ke dalam bentuk teknologi budidaya yang efisien berbasis ekologi (lahan dan iklim) untuk digunakan sebagai arah dan strategi pengembangan cengkeh dimasa yang akan datang.Kata kunci : Cengkeh, teknologi, ekologi, kesesuaian lahan